2013
DOI: 10.1039/c3nr00917c
|View full text |Cite
|
Sign up to set email alerts
|

Environment-mediated structure, surface redox activity and reactivity of ceria nanoparticles

Abstract: Nanomaterials, with potential application as bio-medicinal agents, exploit the chemical properties of a solid, with the ability to be transported (like a molecule) to a variety of bodily compartments. However, the chemical environment can change significantly the structure and hence properties of a nanomaterial. Accordingly, its surface reactivity is critically dependent upon the nature of the (biological) environment in which it resides. Here, we use Molecular Dynamics (MD) simulation, Density Functional Theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 33 publications
4
65
0
1
Order By: Relevance
“…21 In this present study, our images of nanostructured TiO 2 are in close accord with experiment ( Figure 4(a,b) and Figure 7(a,b)). The close comparison with HRTEM acts as a validation of the model.…”
Section: ■ Resultssupporting
confidence: 93%
“…21 In this present study, our images of nanostructured TiO 2 are in close accord with experiment ( Figure 4(a,b) and Figure 7(a,b)). The close comparison with HRTEM acts as a validation of the model.…”
Section: ■ Resultssupporting
confidence: 93%
“…In the anion Frenkel type defect, an oxygen ion is displaced from its lattice position to an interstitial position, hence creating a vacancy at its original position and a defect at the interstitial site [39][40][41]. In general, the formation of these defects does not influence Figure 1 Fluorite structure of ceria.…”
Section: Crystallography and Defect Structure Of Ceriamentioning
confidence: 95%
“…In the past years, several studies based on atomistic calculations have also suggested the presence of additional defects in the ceria lattice, such as interstitial and Schottky disorder [29,41,45]. An interstitial defect is the displacement of both a cerium and two oxygen ions to form interstitial sites, for example, Figure 2 Possible types of point defects in the CeO 2 lattice.…”
Section: Crystallography and Defect Structure Of Ceriamentioning
confidence: 97%
“…The water dissociation on (111) surface was found to be much less stable than on (100) one, and water is predicted to recombine and leave the surface above 300K [96]. Further simulations predicted higher activities of ceria nanoparticles towards oxygen release, when immersed in water because the water quenches the coordinative unsaturation of surface ions [97].…”
Section: Interatomic Potentials and First Principles Studies Of Bulk mentioning
confidence: 97%